THE EFFECT OF LIQUIDITY AND PROFITABILITY TO RETURN ON INVESTMENT (Journal of Technology and Operations Management, 2017)
The purpose of this research is to know empirically about influence Liquidity and Profitability to Return on Investment. In this research, the method used the quantitative approach with the data source used is the financial statements 2010 - 2015. The study area is the Bank Mega located in South Jakarta. Data analysis technique were computed using multiple regression, correlation coefficient, determination coefficient, partial test and simultaneous test. Statistical results indicate there is showed that partially and simultaneously there is a significant effect of Liquidity and Profitability to Return on Investment (ROI).